2017
DOI: 10.1155/2017/5952897
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Antiamnesic Effects ofMitragyna inermisWilld (Rubiaceae) on Scopolamine-Induced Memory Impairment in Mice

Abstract: Aim. To assess memory improvement and neuroprotective and antioxidant effects of Mitragyna inermis (M. inermis) leaf decoction on the central nervous system. Methodology. Leaf decoction of M. inermis was tested on learning and memory in normal and scopolamine-induced cognitive impairment in mice using memory behavioral tests such as the Morris water maze, object recognition task, and elevated plus maze. Oxidative stress enzymes—catalase, superoxide dismutase, and the thiobarbituric acid reactive substance, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 60 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…After 5 min, rats were removed from the maze and returned to their home cage. The maze was then cleaned with a solution of 70% ethyl alcohol and permitted to dry between tests [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 5 min, rats were removed from the maze and returned to their home cage. The maze was then cleaned with a solution of 70% ethyl alcohol and permitted to dry between tests [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in many neurological disorders, the cognitive functions of patient might be affected. For example, Alzheimer’s disease (AD) is the most common cause of dementia and is characterized by memory loss and cognitive impairment [ 11 , 12 ]. Cognitive functions can be impaired in other neurological disorders such as Parkinson’s disease, multiple sclerosis and stroke [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased TBARS activity has been shown to be an important marker for in vivo lipid peroxidation in the learning and memory deficient mouse brains. In addition, it has been reported that haloperidol significantly increases TBARS activity in the hippocampus and frontal cortex 11,20 . From the results we know that standard-1 decrease the TBARS level in brain, but test substance reduces the level of TBARS in dose dependent manner.…”
Section: Discussionmentioning
confidence: 98%